Maritime Economics : A Macroeconomic Approach - Karakitsos, Elias; Varnavides, Lambros; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book analyses shipping markets and their interdependence. This ground-breaking text develops a new macroeconomic approach to maritime economics and provides the reader with a more comprehensive understanding of the way modern shipping markets function.
Keywords: Transportation; International business enterprises; Investment banking; Securities; Industrial organization; Macroeconomics; International economics; Economics; International Economics; Industrial Organization; International Business; Macroeconomics/Monetary Economics//Financial Economics; Investments and Securities; Transportation